1997
DOI: 10.1046/j.1365-2141.1997.2743091.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of prior therapy on progenitor cell yield: use of a chemotherapy scoring system

Abstract: Summary.A quantitative analysis of peripheral blood stem cell (PBSC) yield, measuring absolute numbers of CD34 þ cells × 10 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 7 publications
6
79
1
Order By: Relevance
“…Progenitor cell mobilization is known to be negatively affected by the number of chemotherapy cycles before PBPC mobilization, pelvic radiotherapy and age. 22,25 The higher mobilization potency of CY+G-CSF observed in a patient population that had been pre-treated with a significantly higher number of chemotherapy cycles as compared to patients mobilized with G-CSF alone, strongly suggests that the priming regimen by itself was determinant in the recruitment of higher amounts of primitive and committed progenitors. Differences in pre-mobilization treatment were only likely to determine the strong inter-patient variability observed in hematopoietic progenitor cell harvests.…”
Section: Discussionmentioning
confidence: 99%
“…Progenitor cell mobilization is known to be negatively affected by the number of chemotherapy cycles before PBPC mobilization, pelvic radiotherapy and age. 22,25 The higher mobilization potency of CY+G-CSF observed in a patient population that had been pre-treated with a significantly higher number of chemotherapy cycles as compared to patients mobilized with G-CSF alone, strongly suggests that the priming regimen by itself was determinant in the recruitment of higher amounts of primitive and committed progenitors. Differences in pre-mobilization treatment were only likely to determine the strong inter-patient variability observed in hematopoietic progenitor cell harvests.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Nonetheless, the former drug is far from being harmless to the bone marrow. 8,13 Lee et al 13 found prior treatment with cisplatin to be a significant independent factor predicting worse HPC collection.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have sought to define parameters associated with a successful PBSC harvest, and factors such as previous chemotherapy, 4,18,19,20 age, 18 and the mobilization procedure 21 were singled out as relevant. A history of extended field radiotherapy was, as expected, also found to profoundly and constantly affect PBSC collection.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated successful PBSC collection rates exceeded 80% in patients with a score ranging from 0 to 15 and were below 20% in patients with a score greater than 25 ( Figure 1). This scoring system allowed three groups to be defined, one with a low (score 0-15), one with an intermediate (score [16][17][18][19][20][21][22][23][24] and the other with a high (score Ͼ25) probability of unsuccessful PBSC harvest.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%